2018
DOI: 10.3390/nu10101381
|View full text |Cite
|
Sign up to set email alerts
|

DKB114, A Mixture of Chrysanthemum Indicum Linne Flower and Cinnamomum Cassia (L.) J. Presl Bark Extracts, Improves Hyperuricemia through Inhibition of Xanthine Oxidase Activity and Increasing Urine Excretion

Abstract: Chrysanthemum indicum Linne flower (CF) and Cinnamomum cassia (L.) J. Presl bark (CB) extracts have been used as the main ingredients in several prescriptions to treat the hyperuricemia and gout in traditional medicine. In the present study, we investigated the antihyperuricemic effects of DKB114, a CF, and CB mixture, and the underlying mechanisms in vitro and in vivo. DKB114 markedly reduced serum uric acid levels in normal rats and rats with PO-induced hyperuricemia, while increasing renal uric acid excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…In another study, Chen, Li, Wu, Li, and Ma (2019) and Chen et al (2013) reported that lemon water and rutin exhibited urate lowering potential in a similar fashion. Previously, many natural products as well as their bioactive compounds are reported to inhibit XOD enzyme potently (Hongyan et al, 2016; Jhang et al, 2016; Kumar et al, 2018; Lee, Kim, Yuk, & Kim, 2018; Lee, Kim, Yuk, Lee, & Kim, 2018; Li et al, 2017; Liu et al, 2019; Mehmood, Zhao, Wang, Nadeem, et al, 2019; Peng, Lin, Zhao, & Sun, 2019; Wan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Chen, Li, Wu, Li, and Ma (2019) and Chen et al (2013) reported that lemon water and rutin exhibited urate lowering potential in a similar fashion. Previously, many natural products as well as their bioactive compounds are reported to inhibit XOD enzyme potently (Hongyan et al, 2016; Jhang et al, 2016; Kumar et al, 2018; Lee, Kim, Yuk, & Kim, 2018; Lee, Kim, Yuk, Lee, & Kim, 2018; Li et al, 2017; Liu et al, 2019; Mehmood, Zhao, Wang, Nadeem, et al, 2019; Peng, Lin, Zhao, & Sun, 2019; Wan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Genome‐wide association studies reported that around 90% hyperuricemia patients exhibit under‐excretion of uric acid. The reabsorption and excretion of uric acid handle by multiple transporters in the intestine and renal tissues such as; URAT1, GLUT9, and breast cancer resistance protein or ATP‐binding cassette, subfamily G, 2 (BCRP, ABCG2) (Ichida et al, 2012; Lee, Kim, Yuk & Kim, 2018; Lee, Kim, Yuk, Lee, et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…DKB114 decreased cellular uric acid uptake in oocytes, and HEK293 cells expressing human urate transporter (hURAT)1 and decreased the protein expression levels of urate transporters, URAT1, and glucose transporter, GLUT9, associated with reabsorption of uric acid in the kidney. DKB114 exerts antihyperuricemic effects and uricosuric effects, which are accompanied by a reduction in the production of uric acid and promotion of uric acid excretion via inhibition of xanthine oxidase activity and reabsorption of uric acid (22).…”
Section: Discussionmentioning
confidence: 99%
“…Co. Ltd, Suwon, Korea, Lot number is BPD170926-1) was prepared as described previously. Briefly, DKB114 was selected and prepared by mixing previously prepared C. indicum flower and C. cassia bark extracts at a weight ratio of 1:2 based on our previous report [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation